Suspected autoimmune myocarditis and cardiac conduction abnormalities with nivolumab therapy for non-small cell lung cancer. (20th July 2016) - Gibson, Robert; Delaune, Jess; Szady, Anita; Markham, Merry
Abstract : Checkpoint inhibitors such as nivolumab represent a novel class of agents that are being increasingly used in the treatment of various cancers. Their toxicities represent unique challenges to the oncologists prescribing them, patients' primary care physicians and other specialists who may encounter these patients during consultations. It is important for physicians to remain vigilant and include autoimmune toxicities in the list of potential differential diagnoses in patients receiving novel cancer therapeutics who present with unusual toxicities. We report the unusual case of a 68-year-old woman with advanced lung cancer on the novel chemotherapeutic Nivolumab whom we suspect developed autoimmune myocarditis with significant cardiac conduction disease as an unintended, and as of yet unrecognised, side effect from this medication.